RELATIONS BETWEEN THE QUALITY OF HEALTH SERVICES WITH OUTPATIENT LOYALTY IN POLY OBGYN RSIA ERIA PEKANBARU IN 2016 - Leon Candra; Rosi Hairati (LPPM Universitas Muhammadiyah Riau, 2017)
Customer loyalty is a person who buys, especially purchase regularly and repeat edly (Hassan, 2008). The purpose of this study is whet her there is a relationship of health service quality and out patient loyalty of poly OBGYN in RSIA Eria Bunda Pekanbaru 2016. This research method is quantitative analytic observational using cross-sectional design, respondents were out patients of poly OBGYN RSIA Eria Bunda Pekanbaru. The study sample as many as 97 out patients. The sampling technique is purposive sampling. The analysisis univariate and bivariate analysis using Chi-square, measuring instruments used were question naires and computerized data processing. The results showed anassociation between tangibles (p value = 0.046 and POR = 2.9), reliability (p value = 0.007, and POR = 4) and empathy (p value = 0.031, and POR = 3.4) with patient loyalty in the Poly Obgyn RSIA Eria Bunda Pekanbaru. The absence of a relationship between responsiveness (p value = 0.079, and POR = 0.3) and assurance (p value = 0.593, and POR = 1.4) with patient loyalty in the Poli OBGYN RSIA Eria Bunda Pekanbaru. Suggested for RSIA Eria Bunda Pekanbaru need to do the training, disseminating feed back, criticisms, and suggestions of the patien/family and need to think about how to suppress deficiencies in service, equipment (tangible ) to improve service quality, and human resources, that are expected to display the superior it service.